2006
DOI: 10.1590/s1519-566x2006000600011
|View full text |Cite
|
Sign up to set email alerts
|

Nucleopolyhedrovirus: scanning electron microscopy technique

Abstract: Neotropical Entomology 35(6):787-790 (2006) Nucleopolyhedrovirus: Técnica de Microscopia Eletrônica de Varredura RESUMO -Um método simples foi desenvolvido para se estudar a forma geométrica do Bombyx mori Nucleopolyhedrovirus múltiplo, BmMNPV, para microscopia eletrônica de varredura. O vírus, pertencente à Família Baculoviridae, foi obtido do fi ltrado, do inóculo e da hemolinfa de lagartas de Bombyx mori (L.) (Lepidoptera: Bombycidae) infectadas. O material foi colocado diretamente sobre o suporte de var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 17 publications
(16 reference statements)
0
8
0
1
Order By: Relevance
“…In the electron micrographs, the polyhedron envelope has a membrane-like structure, as shown in Figure 6. The BmMNPV polyhedron ranges from 2.5 to 4.5 µm in diameter and has a truncated octahedron geometric shape (Torquato et al, 2006b). Hong et al (2000) suggest the existence of genetic variation in the polyhedron geometric shape of BmNPV and that this is specific for each viral lineage.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the electron micrographs, the polyhedron envelope has a membrane-like structure, as shown in Figure 6. The BmMNPV polyhedron ranges from 2.5 to 4.5 µm in diameter and has a truncated octahedron geometric shape (Torquato et al, 2006b). Hong et al (2000) suggest the existence of genetic variation in the polyhedron geometric shape of BmNPV and that this is specific for each viral lineage.…”
Section: Resultsmentioning
confidence: 99%
“…Reddy and Locke (1990) investigated the behavior of gold particles on the BL of Calpodes ethlius (Lepidoptera: Hesperiidae) larvae, and showed that particles smaller than 15 nm crossed the BL of certain tissues, such as fatty, epidermal and pericardial ones, whereas particles larger than 6 nm were retained in the silk gland, in the Malpighian tubule and in the muscle BL. BmMNPV virions have an approximate mean diameter of 95 nm and length of 315 nm (Torquato et al, 2006b), making the passage of BV through the silk gland BL difficult.…”
Section: Resultsmentioning
confidence: 99%
“…Geralmente, oscilações de temperatura, alimentação com folhas de má qualidade e irregularidade nos horários de alimentação podem favorecer a maior incidência da virose (Hanada;Watanabe, 1986). Um vírus do gênero Alphabaculovirus chamado de nucleopolyhedrovirus, subgrupo múltiplo de B. mori (BmMNPV), foi isolado no estado do Paraná e apresenta-se altamente patogênico, em função da presença de vários nucleocapsídeos por vírion e elevada mortalidade em curto espaço de tempo Torquato et al, 2006).…”
Section: Entomopatógenos Que Acometem a Criação De B Moriunclassified
“…Viral morphology with and without LASN treatment was elucidated following SEM [12,13] with minor modifications in the protocol. First, 0.5 mg of dry NP powder was added in 1.5 ml of ethanol and made an ethanolic solution of LASN.…”
Section: Bmnpv Polyhedra-np Complex Incubationmentioning
confidence: 99%